An Analysis of School Principal’s Managerial Competencies on Accreditation Ranking - Yuserizal Bustami; Eka Putra (Jurnal Educatio FKIP UNMA, 2023)
Principals are educational institution leaders responsible for the management and growth of their schools. Principals with solid managerial skills can motivate school staff to work effectively and efficiently, thereby enhancing the performance of teachers and support staff. This study's objective was to identify variances in the managerial competence of school principals based on their accreditation ratings. This research employed a cross-sectional survey methodology. One hundred sixteen school principals participated in the survey. For data collection, researchers utilized the school managerial competence research scale. Developed hypotheses are evaluated using the ANOVA technique. The study results indicate that the managerial competency achievements of A-rated school principals are in the very high category, while those of B- and C-rated schools are in the high category. ANOVA analysis demonstrates differences in the managerial skills of school principals based on their accreditation ratings. This finding proves that the managerial competence of principals in accredited A schools is better than those leading schools that are accredited B and C. The ability of the principal to apply leadership principles will have a positive impact on the management of educational institutions. School principals need to increase their managerial competence through training, competency evaluation, and a greater understanding of the curriculum and education programs. In addition, it is necessary to recruit school principals objectively.